DEVELOPMENT OF DIAGNOSTIC REFERENCE LEVELS (DRL) OF PATIENTS X-RAY EXPOSURE IN DIAGNOSTIC RADIOLOGY - A. V. Vodovatov; S. A. Kalnitsky; M. I. Balonov; I. G. Kamyshanskaja (Радиационная гигиена)
We introduce a system of Diagnostic Reference Levels (DRLs) for patients medical exposure for national health care practice implementation. DRLs are an effective way of the patient radiation protection through the optimization of the medical exposure. The paper discusses and compares different methods of determining the DRLs based on measured and/or calculated quantities of patient’s dose: dose area product (DAP), entrance surface dose (ESD) and an effective dose. Distributions of different dose quantities in different Saint-Petersburg clinics are shown on the example of chest PA examinations. The results are compared with the data from other sources. Regional DRLs for Saint-Petersburg are proposed.